Antifungal Activity of Leaf Extract of Alchornea cordifolia Against Aspergillus flavus the causal Agent of Yam Tuber Rot: Aktivitas Anticendawan Ekstrak Daun Alchornea cordifolia terhadap Aspergillus flavus Penyebab Busuk Umbi Ubi Jalar - Enyiukwu, David; Amadioha, Anderson Chidi; Bassey, Inemesit Ndarake (Jurnal Fitopatologi Indonesia, 2023)
Rots and mycotoxin contamination of agro-produce are prevalent in tropical world. Aspergillus flavus is a major mycotoxigenic rot contaminant of tubers in Abia state, Nigeria. Consumption of mycotoxin contaminated foodstuffs accounts for 25% of medically important human diseases in Nigeria. The objective of this study was to assess antifungal activity of Alchornea cordifolia against A. flavus a mycotoxigenic rot pathogen of stored tuber produce both in vitro and in vivo.  Isolates were made from rotted yam tubers and pathogenicity test carried out to confirm A. flavus as pathogen. Five concentrations (100-500 mg mL-1) of methanol leaf extracts of the plant and thiophanate-methyl–a standard fungicide–were evaluated against the growth of the fungus in culture and pathogen-induced rot development and spread in vivo. The experiment was made up of 7 treatments and 3 replicates laid out in CRD. The plant leaf extract demonstrated varying levels of inhibition of A. flavus in vitro and rot development and spread in living tissues of yam. About 56.38%–68.22% and 67.245–80.01% inhibition was recorded by 100 mg mL-1 and 500 mg mL-1 of A. cordifolia extract for spore germination respectively whereas the same concentrations reduced rot development from 60% in the control experiment to 21.80% and 12.10% respectively which compared favorably (P